Practices to Minimize Flooding Damage to Commercial Vegetable Production - Guodong Liu; Yuncong Li; Xiangju Fu (EDIS)
Flooding is a major risk for commercial vegetable production in south Florida, especially in the south Dade County area. Flooding causes oxygen deficiency, or hypoxic stress, causing the plants to produce less energy. This shortage in energy prevents the absorption of nutrients like nitrogen, phosphorous, and potassium. This revised 4-page fact sheet discusses several different management practices for overcoming flood damage, including the use of nitrogen and potassium fertilizers, oxygen fertilizers, growth regulators, and fungicides. Written by Goudong Liu, Yuncong Li, and Xiangju Fu, and published by the Soil and Water Science Department, December 2015.